Pemberdayaan Ibu-Ibu PKK Melalui Pembuatan Tote Bag Batik Ecoprint dengan Teknik Pounding di Desa Troso - Widyanti, Alfira; Andalesta, Graseva; Munahefi, Detalia Noriza; Firdaus, Yulizar; Qays, Ghaitsa Fasya (Universitas Negeri Semarang, 2025)
Troso is one of the villages in Karanganom District, Klaten Regency. Farmers are the majority of the community's livelihoods. So far, the potential of Troso Village has not been utilized optimally, such as the utilization of plants in the surrounding environment. Existing plants can be used as ecoprint batik. Empowering PKK mothers through making ecoprint batik tote bags with the pounding technique is one of the strategic efforts in developing their skills and creativity, while preserving the environment, which of course also utilizes plants in the Troso Village environment. The main objective of this program is to equip PKK mothers with the skills of making tote bags using ecoprint batik and pounding techniques, which can increase their household income. The objects of this empowerment are PKK mothers who are involved in practical training and production. The methods used are training and demonstration methods. The training process includes education and is continued with direct demonstrations, independent practice, and guidance in tote bag design. The results of this program include improving skills in handicrafts and optimizing the use of plants in the Troso Village environment to become ecoprint motif materials. In addition, this program has also succeeded in strengthening awareness of the preservation of batik culture and environmental sustainability. If this is done sustainably, it can be a new business opportunity for the Women of Troso Village.